Local Government and Climate Change Policy Implementation in China: Lessons for Vietnam - Hoai Son, Ngo; Hoa, Nguyen Van (VNU Journal of Science: Policy and Management Studies, 2018)
Abstract : This paper applies desk research method with the use of available literature about China’s Climate policy implementation at local government to review the vital role of local government in implementing this policy. The paper then analyses China’s practices and draws four important lessons for Vietnam. Firstly, there is a need to combine top-down and bottom-up approaches in policy implementation. Secondly, the local government should focus on integrating the climate change response targets into its scio-economic development strategy and plans. Thirdly, it is necessary to raise the important roles of NGOs as well as generate favourable conditions for their effective interaction with local government during policy implementation. Fourthly, the awareness and perception of the local government about climate change is a crucial factor to ensure success of climate change policy implementation. Keywords: Local government, climate change, China. References [1] Chmutia, K., Zhu, J., Riffat, S. (2012), An analysis of climate change policy-making and implementation in China, International Journal of Climate Change Strategies and Management, Vol. 4, No.2, 2012, pp. 138-151 [2] Bjorkum, I. (2005), China in the International Politics of Climate Change: A Foreign Policy Analysis (FNI Report 12/2005), available at: www.fni.no/doc&pdf/FNI-R1205.pdf (accessed 6 April 2008). [3] Freestone, D. and Streck, C. (Eds) (2005), Legal Aspects of Implementing the Kyoto Protocol Mechanism: Making Kyoto Work, Oxford University Press, Oxford. [4] Heggelund, G. (2005), International CER Market and CD Experiences in Developing Countries (Final Report), CPR/01/002 and CPR/02/H02 Building Capacity for the CD in China, FNI. [5] Fei Teng & Alun Gu (2007) Climate change: national and local policy opportunities in China, Environmental Sciences, 4:3, 183-194, DOI: 10.1080/15693430701742735. [6] Tsang, S. & Kolk, A. (2010), The evolution of Chinese Policies and Governance Structures on Environment, Energy and Climate, Journal of Environmental Policy and Governance, Vol.20, pp.180-196 [7] Pressman J, Wildavsky A. (1984), How Great Expectations in Washington are Dashed in Oakland; Or, Why It’s Amazing that Federal Programs Work at All, This Being a Saga of the Economic Administration as Told by Two Sympathetic Observers Who Seek to Build Morals on a Foun- dation of Ruined Hopes. University of California Press: Berkeley, CA [8] Schreurs, M. (2017), Multi-level Climate Governance in China, Jouranl od Environmental Policy and Governance, Vol. 27, pp. 163-174. DOI: 10.1002/eet.1751 [9] Kostka, G. (2014), Barriers to the implementation of Environmental Policies at the Local Level in China, Policy Research Working Paper 7016, World Bank Group, Development Research Group Environment and Energy Team, August 2014. [10] Kostka, G. and Mol, A.P.J. (2013) Implementation and Participation in China's Local Environmental Politics: Challenges and Innovations, Journal of Environmental Policy & Planning, 15 (1), 3-16. [11] Gao, Ruge (2013). Rise of Environmental NGOs in China: Official Ambivalence and Contested Messages. Journal of Political Risk, Vol. 1, No. 8, December. Available at http://www.jpolrisk.com/rise-of-environmental-ngos-in- china-official-ambivalence-and-contested-messages. [12] Trần Ngọc Thêm (1999), Tìm về bản sắc văn hoá Việt Nam, NXB Văn Hoá, Hà Nội